Self-Confidence, Perceived Exam Anxiety and Academic Success in Physical Education and Sports School Students - Aybüke ŞAHSUVAR; Neslişah AKTAŞ ÜSTÜN (ümit doğan üstün, 2023)
The present study aimed to analyze self-confidence, perceived exam anxiety and academic success of Hatay Mustafa Kemal University School of Physical Education and Sports students according to personal features and reveal the relationships between the variables. The study was designed according to cross-sectional quantitative model and 198 subjects selected according to the simple random sampling method participated in the study. The data were collected with the "Self-Confidence Scale" and the "West-Side Exam Anxiety Scale" as well as the personal information form. SPSS 23 package program for Windows was used to evaluate the data. In the data analysis, the internal consistency coefficients for the data collection tools were calculated and the mean, standard deviation, kurtosis, and skewness values were examined. In the study, independent samples t-test, one-way analysis of variance test and Pearson Correlation analysis were used as hypothesis tests at 95% confidence interval. As a result, the present study showed that there was no significant difference in the self-confidence of Hatay Mustafa Kemal University School of Physical Education and Sports students in terms of gender, department, licensed sports, and preferred sports branch, whereas external self-confidence increased as the grade point average increased. Besides, there was no significant difference in the perceived exam anxiety of the participants in terms of gender, licensed sports, and the preferred sports branch; on the other hand, physical education teaching department students had lower test anxiety. Last, while self-confidence and grade point average increased, test anxiety decreased.